Beyond gender - Sisfontes Guilarte, Pablo (2011)
The purpose of this essay is to describe, based on the everyday life, the influence of words in popular songs and highlight, at the same time, that what we see, hear and live everyday are powwerful tools of long-lasting learning in the construction of gender-related cultural representations. The study emphasizes the influence of popular song lyrics in the construction of male identity, and how that determines the relations between men and women. It points out the need to break stereotypical gender models, which generate violence against women and some men in the context of a patriarchal society, to pursue a more democratic and equitable society based on the principle of equality.